Development of an Online School Document Processing for Registrar and Cashier in Pangasinan State University Alaminos City Campus (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The main offices that require improvement are the Registrar and Cashier offices of Pangasinan State University – Alaminos City Campus. These offices are responsible for the requests for documents transactions among the students. The manual and/or semi-manual procedures and usage of these offices are inefficient and result in delays and inconsistencies. Thus, this study aims to create an effective and efficient way of addressing this problem by creating an "Online School Document Processing System." The system was created by utilizing a Web-based platform where students can access the documents they need and perform payment verification. The system can contribute greatly to the efficient management of documents by the university. Furthermore, based on the testing and assessment conducted, the system proves that it is an effective and efficient way of creating and utilizing documents. The system can help the offices of the registrant and cash register with their tasks and may result in more student satisfaction. Conclusion Thus, this study proves that the creation and usage of the system are indeed effective. The system may help the offices of the registrant and cash register with their tasks and may result in more student satisfaction. The system can also contribute.